.5-x-x=-1

Simple and best practice solution for .5-x-x=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5-x-x=-1 equation:


Simplifying
0.5 + -1x + -1x = -1

Combine like terms: -1x + -1x = -2x
0.5 + -2x = -1

Solving
0.5 + -2x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5' to each side of the equation.
0.5 + -0.5 + -2x = -1 + -0.5

Combine like terms: 0.5 + -0.5 = 0.0
0.0 + -2x = -1 + -0.5
-2x = -1 + -0.5

Combine like terms: -1 + -0.5 = -1.5
-2x = -1.5

Divide each side by '-2'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 15x^3+8x^2-x=0 | | 5u-34=-8(u+1) | | 8x-8=62 | | 3x^2-12x=8-2x | | x(2x+-9)=45 | | -9/5-2/3u=-1/2 | | (X-2)=-1/4(x-8) | | 9x-3y=101 | | -2(x-4)+3(x+1)=17 | | 4n+4=34-2n | | 11g=66 | | N=-1.825 | | 6b+9h= | | (3x^2-6x-9)/(x-5) | | 2z/7-1=8 | | 28-4v=2v+4 | | -3x+17-5x=12-(6x+3) | | f(-49)=-5x+1 | | 3/4=7/x-9 | | 5x-2y+3x+y= | | -21=-9+4x | | 2x+10=5x+10-3x | | f(-2)=x^2-5 | | 8-2+a-9a= | | F(-2)=5x^2-7x+10 | | (4x+6)=(3x+9) | | (6-15)*(4+5)= | | 10x-2(x+4)=4x-7 | | 40+50m=365 | | x+x+89=180 | | 5+11p=71 | | 128=2(6y-2) |

Equations solver categories